ASSESSMENT OF BIOTECHNOLOGICAL POTENTIAL OF MICROORGANISMS CULTURES PROMISSING FOR SUPRESSING ANTIBIOTIC-RESISTANT STRAINS - Anuarbekova , S.S.; Jumagaziyeva , A.B.; Amangeldinova , D.K.; Sharova , D.E.; Kanafina , M.A.; Nurgalieva , R.K.; Alzhanova , G.S.; Tynybayeva , I.K.; Sadykov , A.M. (Eurasian Journal of Applied Biotechnology, 2024)
One of the problems in global practical medicine is antibiotic-resistant strains. The problem is that pathogens are resistant to a number of antibacterial drugs and this makes treatment difficult, which can be long and/or ineffective. One solution is to develop drugs based on bacterial lysates. In this article, the objects of study are producers of extended spectrum β-lactamases - Enterobacteriaceae, Acinetobacter, Pseudomonas, Staphylococcus, Haemophilus, Streptococcus. We assessed the survival, antibiotic resistance and biological compatibility of 25 microbial cultures. Cultures have acceptable viability numbers reguired for industrially valuable strains: more than 106 CFU/ml (109 – 1010 CFU/ml). Antibiotic resistance to various groups of is antibiotics was studied: carbapenems, fluoroguinolones, cephalosporins, macrolides, aminoglycosides, penicillins, chloramphenicols. The choise of antibacterial drugs is based on the freguent use of these antibiotics. The spectrum of antibiotic resistance of each strain is different, from one antibiotic (Ps. aeruginosa 13) to ten antibiotics (S. pneumoniae 5). Cultures are resistant to amoxicillin, ampicillin, benzylpenicillin, erythromycin and cephalosporins. The strains are mostly biocompatible with each other and have antibiotic resistance to a number of antibacterial drugs.